2021
DOI: 10.1007/s11606-021-07085-w
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Prescription Opioid Tapering Research: the EMPOWER Study and a Coproduction Model of Success

Abstract: Patients with chronic pain experience stigma within the healthcare system. This stigma is compounded for those taking long-term prescription opioids. Often, public messaging and organizational policies have telegraphed that opioid treatment is a problem to be solved by focusing only on medication reduction efforts. Lack of data has contributed to misperceptions and poor opioid policies. In part, data collection remains poor because patients feel fractured from systems of care and are often not interested in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…We believe that endorsing patient control and agency during opioid taper is critical for optimal patient outcomes. 26 Currently, this individualized consensual approach is being extended to a large 4-state trial. 10 To encourage patient retention and improvement, weekly surveys are used to rapidly identify and address patient discomfort and distress, including pausing or stopping their taper or adding adjuvant medications.…”
mentioning
confidence: 99%
“…We believe that endorsing patient control and agency during opioid taper is critical for optimal patient outcomes. 26 Currently, this individualized consensual approach is being extended to a large 4-state trial. 10 To encourage patient retention and improvement, weekly surveys are used to rapidly identify and address patient discomfort and distress, including pausing or stopping their taper or adding adjuvant medications.…”
mentioning
confidence: 99%
“…Nemours studies reported that individuals who acquire these self-management skills are able to take an active role in managing their condition and adopting a healthy lifestyle. 16 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“… 32 Recent evidence also suggests that action planning is considered one of the effective elements of the CDSMP for improving self-efficacy and the motivation for behavioral changes. 16 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…The perspectives and original research articles in this supplement share a focus on the lived experience of the participants of engagement, as well as exploring barriers and facilitators that can affect group cohesion. [5][6][7][8][9][10][11][12][13][14][15] Many of the studies measured satisfaction with the engagement process as a key outcome. One strong commonality amongst the perspectives and original research articles is the use of descriptive approaches, often outlining the temporal flow of the engagement process for a project and frequently accompanied by qualitative and/or mixed methods.…”
Section: What We Discovered From This Supplementmentioning
confidence: 99%